Idle Time in Prison: The Emotional, Social, and Practical Impacts of Incapacitation - Fox, Kathryn J. (Journal of contemporary criminal justice, 2024)
The existing research on the prevalence and impact of boredom in prison is extensive. The passing of time and its unique meaning in a prison context has been documented. Missing from the research is an analysis of the ways in which “warehouse” prisons do not prioritize meaningful activity, even when there is agreement between correctional staff and incarcerated individuals about the negative impacts of idle time in prison. Based upon research in a Vermont men’s prison, we use data involving incarcerated individuals and correctional staff, including focus groups and interviews, surveys, and qualitative feedback on the meaning of the survey results. Synthesizing these various data forms, this article focuses on the relationship between incarcerated persons’ perceptions of how they are able to spend their time in the facility, how prepared they feel for release, lack of opportunities to earn money, and the impacts on their wellbeing. “Warehousing,” as it is known in prison terms, contributes to the sense of hopelessness that incarcerated people feel, and acknowledgment by staff that the prison function is incapacitation. As this project is aimed at improving prison climate, addressing idle time in prison emerged as a high priority.